Does working at a start-up pay off? - Daniel Fackler; Lisa Hölscher; Claus Schnabel; Antje Weyh (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2020)
Using representative linked employer-employee data for Germany, this paper analyzes short- and long-run differences in labor market performance of workers joining start-ups instead of incumbent firms. Applying entropy balancing and following individuals over ten years, we find huge and long-lasting drawbacks from entering a start-up in terms of wages, yearly income, and (un)employment. These disadvantages hold for all groups of workers and types of start-ups analyzed. Although our analysis of different subsequent career paths highlights important heterogeneities, it does not reveal any strategy through which workers joining start-ups can catch up with the income of similar workers entering incumbent firms.
Keywords: J31; J63; L26; M51; 330; startups; young firms; wages; linked employer-employee data